'Nothing could be more pernicious': King James II and parliament at King's Inns, Dublin, 1689. (2nd September 2017) - Kenny, Colum
ABSTRACT: This article concerns the only session of the Irish parliament during the seventeenth and eighteenth centuries at which most members shared the Roman Catholic religion of the majority of Irish people. It explores for the first time the significance of that parliament's meeting in 1689 at an inn of court, a location at which members never before or afterwards convened, and highlights in this context the leading role of judges and senior law officers in its affairs there. Attended by James II, it was also the only Irish parliament opened by a king of England and Ireland before the institution's abolition in 1800. Dismissed by its Williamite detractors as 'pretended' and even by some Jacobites as 'pernicious' for distracting King James from military objectives, the assembly of 1689 was later depicted by nostalgic nationalists as 'the patriot parliament'.